Education In The Arab Gulf States and the Arab World: An Annotated Bibliography by Nagat El-Sanabary. (New York: Garland Publishing, Inc., 1991. 572 pages.) (American Journal of Islam and Society, 2001)
Education In The Arab Gulf States And The Arab World: An AnnotatedBibliography is divided into six parts. Each part contains between one toten chapters according to the topic. In the preface, the author mentions thatshe includes all references found in US libraries and the Libraryof Congress and does not include references from Arab countries. Shealso mentions that she was "selective" in her choices of what to includeand what not. For example, literature from the social sciences thatcontained a lot of stereotyping and biased information about Islam, Arabsand Arab society in general was excluded. Unpublished works alsowere not included. The author then describes her method of listing thebibliography: when there was literature available on the Arab world ingeneral, she included that, and then she would list the seven Gulf States inalphabetical order. If there were no references for a country, then thecountry is not mentioned and she jumps to the next country in that order.Part One contains only one chapter, which is the introduction. ElSannbarypresents an historical overview of the Gulf States, which is herfocus: Bahrain, Iraq, Kuwait, Oman, Qatar, Saudi Arabia and the UnitedArab Emirates. A map of the region is presented on page four. She surveysthe history and the present conditions of the seven states economically,politically and educationally. The rest of the chapter includes a one-pagesummary on all the topics, which are mainly the chapters that follow.Part Two comes under the heading "General Background andResources", and consists of three chapters. Chapter Two, "Context ofEducation", contains 165 entries. It starts with the Arab World (entry 1-52)followed by Bahrain (52-60), Iraq (61-76), Kuwait (77-95), Oman (96-102), Qatar (103-108), Saudi Arabia (109-154), and the United ArabEmirates, (155-165). This is the system followed throughout the wholebook. When there is no literature available on a country, it is notmentioned. Chapter Three, "Bibliographies and References", starts withgeneral references (166- 215), and then is followed by Iraq (216), Kuwait(217), Oman (218-2190, Qatar (220-223), United Arab Emirates (224)and finally educational references (225-259). Chapter Four, "Religion andEducation," lists 120 entries (260-380) ...